Pelatihan Web Log sebagai Media Publikasi Sekolah dan Kegiatan Belajar Mengajar di SDN 1 Ngampel - Moch Yusuf Asyhari; Juwari Juwari; Abdul Rozaq; Kelik Sussolaikah (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
The pandemic makes the utilization and competition of information and communication technology has increased. One of the ways to maintain the existence of schools are publication media of more varied school information and teaching-learning activities media. The purpose of this training program is to provide additional expertise for creating inexpensive and fast publications media and teaching-learning media. The offered solution is the use of web logs from Google which is often known as Blogger. Blogger offers a free and easy web log feature. The training was carried out directly at the Sekolah Dasar Negeri 1 Ngampel by using lectures and demonstrations method. There are several parts in this training, web log making, web log management, and also web log analysis. The results of this training show that the participants have succeeded in having their own web logs which are ready to be further managed and analyzed on a regular basis. The use of web logs can be used for various needs, including as a publication media and supporting teaching-learning activities.